Global race, nationality, and gender conflicts desai and adiga works - MD YASIN (International Journal of Multidisciplinary Research and Studies, 2021)
The word "subaltern" refers to individuals or groups who are considered to be lower in rank and status than others due to factors such as race, class, caste, gender, religion, ethnicity, or sexual orientation, amongst other factors. It is a situation or circumstance in which an individual does not have a voice or any agency in the structure of society. As a result, subalterns are located on the periphery of society. Antonio Gramsci, an Italian Marxist historian and political activist, is credited with being the first person to use the term "subaltern." He did so in his article "Notes on Italian History," which was later published in his well-known book, Prison Notesbooks (1919-1935). Gramsci used the term to refer to any "low rank" person or group of people in a specific society who were suffering under the hegemonic domination of the ruling power. The critical field of study known as Subaltern Studies first set out with the intention of rereading colonial historiography in a manner that went against the grain, and it eventually made its way into the territory of postcolonial critique. In the years 1979 and 1980, many historians, including Sahid Amin, Dipesh Chakrabarty, Partha Chatterjee, David Arnold, David Hardiman, Gyanendra Pandey, and others, came together to create a unique organization known as the Subaltern Studies Group. Ranajit Guha served as the group's head. According to Guha's definition, the primary objective of the organization was "to foster a systematic and informed debate of subaltern topics in South Asian Studies," with the secondary objective being "to remedy elitist prejudice prevalent of much research and academic work" (Guha vii). After the publication of Gayatri Chakravorty Spivak's influential essay "Can the Subaltern Speak?," the term "subaltern" gained a great deal of renown and relevance in the academic community (1988).